Managing Judicial Change through Mediation — Part 1 - Zalar, Ales; Chitashvili (Translator) , Natia; Uznadze (Translator), Nana (Alternative Dispute Resolution Yearbook, 2022)
The Paper is a translation of Alesh Zalar's article from the publication: Zalar, Ales (2004), Managing Judicial Change through Mediation — Part 1, Case Study of Court-Annexed Mediation, ADR Bulletin: Vol. 6: No. 8, Article 3. Translation is performed by Natia Chitashvili (Doctor of Laws, Associate Professor at Ivane Javakhishvili Tbilisi State University Faculty of Law, Member of Contemporary Private Law Institute, Executive Board Member of Mediators Association of Georgia, Mediator, Mediator of Collective Labour Disputes, Trainer and Assessor of Mediator Candidates, Executive Director of TSU National Center of Alternative Dispute Resolution) and Nana Uznadze (Certified Candidate of Mediator of LEPL Mediators Association of Georgia, Intern, Intern of Ivane Javakhishvili Tbilisi State University National Center for Alternative Dispute Resolution).